The Addition Of Vitamin E In Fish Diet For Gonadal Maturity Of Beardless Barb (Cyclocheilicthys apogon, Val. 1842) - Freddy Ferry Lumban Gaol; Hamdan Alawi; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The addition of vitamin E in fish diet for the gonadal maturity of beardless barb (C. apogon Val 1842) was carried out in fish Hatchery and breeding laboratory, Universitas of Riau from July to october 2015. The brooders collected from Kampar river were acclimitized for several weeks before used. The fish were reared in 12 weeks in tool recirculated water system fiber glass tanks at stocking density of 7 fish/tank. The fish were fed with dry pelled containing 35% protein at satiation. The experiment used a completely randomized design and each treatment had three replicates. The treatment were the dosage of Vitamin E i.e. P0 (0 mg/kg) as control, P1 (100 mg/kg), P2 (200 mg/kg), P3 (300 mg/kg). Result of experiment showed that the addition of 300 mg Vit. E / kg feed was better than dosage, in term of the number of fish reaching mature level (Fourth Stage) (7 fish), Gonad Somatic Index (7,93 %), Fecundity (2678 eggs) and egg diameter (0,706 mm)Key words :Beardless Barb (C. apogon, Val. 1842) Vitamin E, Reproduction quality